KEMITRAAN PEMERINTAH KOTA, LEMBAGA PERBANKAN DAN WAJIB PAJAK DALAM PEMBAYARAN PAJAK BUMI DAN BANGUNAN DI KOTA CIMAHI - Candradewini, Candradewini; Kurniati, Poni Sukaesih (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
Central government policy delegates the management of Land and Urban Building Tax (PBB-P) requires local governments to improve themselves. This is to optimize the acceptance of the tax as the Local Revenue (PAD). This study aims to explain the partnership built by Cimahi City Revenue Service with Banking Institution and taxpayers in performing the payment of land and urban building tax in CImahi City. The research method used qualitative approach. This approach is intended to reveal the phenomenon of partnership woven by the parties that are partnering Department of Revenue, Banking and Society. Informants in this study is the head of the Revenue Service. Representatives of banking and public taxpayers namely the land and urban building tax. To ensure the validity of data used triangulation technique. The results show that in general the partnership works well is evidenced by the increased acceptance of tax and better communication among the partners. Taxpayers awareness to make payments through banks also increases. It also shows the quality of partnership achieving the expected results. Keywords: partnership, goverment, banking, taxpayers